Effect of mortar age on the textile-to-mortar bond behavior - Esfahani, Ali Dalalbashi (2020)
Current Topics and Trends on Durability of Building Materials and Components: Proceedings of the XV edition of the International Conference on Durability of Building Materials and Components (DBMC 2020)